Discovery of the twisted-wing parasite family Myrmecolacidae (Insecta: Strepsiptera) from China, with description of two new species of the genus Myrmecolax Westwood, 1861 - Lu, Xiumei; Liu, Xingyue (Zootaxa, 2014)
The twisted-wing parasite family Myrmecolacidae is recorded from China for the first time based on the discovery of the genus Myrmecolax Saunders. Two species of Myrmecolax are described as new to science, Myrmecolax pachygnathus sp. nov. and Myrmecolax arcuatus sp. nov..